Integration of Steel Slag and Green Compost Enhances Tomato Growth, Physiology, Water use Efficiency, and Antioxidant Responses Under Water-Deficit Stress in Arid Conditions - Farid Errouh; Abdelhamid Aouabe; Lahoucine Ech-Chatir; Nizar El Mazouni; Julio Cesar Rodriguez; Salah Er-Raki; Hassan Chagiri; Hicham Khalisse; Brahim Oudra; Abdelilah Meddich (Journal of Soil Science and Plant Nutrition, 2026)

A phenology-weighted composite agricultural drought index for rainfed croplands in Morocco - Cheik Parfait Dieudonné Nacro; Abdelghani Chehbouni; Gohar Ghazaryan; El Houssaine Bouras; Riad Balaghi; Youssef Bammou; Samia Hasmi; Abdelhafid El Alaoui El Fels; Salah Er-Raki; Abdelhakim Amazirh (Remote Sensing Applications: Society and Environment, 2026)

Integrating arbuscular mycorrhizal fungi and compost to enhance tomato quality, antioxidant system, and soil functioning under deficit irrigation in mediterranean field conditions - Fatima-Ezzahra Soussani; Chayma Ikan; Naira Sbbar; Redouane Ouhaddou; Abderrahim Boutasknit; Lahoucine Ech-chatir; Farid Errouh; Julio Cesar Rodrigez; Nizar El Mazouni; Salah Er-Raki; Rachid Benkirane; Abdelilah Meddich (Plant and Soil, 2026)

Assessment of the potential of sub-diurnal in situ C-band radar data for monitoring maize crop in semi-arid regions - Abdelhafid Elallaoui; Pierre-Louis Frison; Saïd Khabba; Adnane Chakir; Valérie Le Dantec; Salah Er-Raki; Nadia Ouaadi; Pascal Fanise; Ludovic Villard; Bénédicte Fruneau; Zoubair Rafi; Jamal Ezzahar; et al. (Remote Sensing of Environment, 2026)

Enhancing Tomato Yield, Fruit Quality, and Soil Fertility with a Single Application of Steel Slag and Green Waste Compost Across Two Cropping Cycles - Farid Errouh; Abdelhamid Aouabe; Lahoucine Ech-Chatir; Redouane Ouhaddou; Chayma Ikan; Abderrahim Boutasknit; Nizar El Mazouni; Julio Cesar Rodriguez; Salah Er-Raki; Hassan Chagiri; Hicham Khalisse; Brahim Oudra; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Beneficial Microorganisms’ Effects on Root Growth and Rhizosphere Enzyme Activity of the Olive Tree Subjected To Water Stress - Naira Sbbar; Soufiane Lahbouki; Abdelhamid Aouabe; Salah Er-raki; Allal Douira; Ahmed El Bakkali; Abderrahim Boutasknit; Cherkaoui El Modafar; Abdelilah Meddich (Journal of Soil Science and Plant Nutrition, 2026)

Role of Arbuscular Mycorrhizal Fungi Associated with PGPR in the Recovery of the Physiological and Nutritional Status of Olive Trees Under Prolonged Drought Stress - Naira Sbbar; Soufiane Lahbouki; Abdelhamid Aouabe; Salah Er-Raki; Ahmed El Bakkali; Abderrahim Boutasknit; Allal Douira; Cherkaoui El Modafar; Abdelilah Meddich (Journal of Soil Science and Plant Nutrition, 2025)

Combined Application of Green Waste Compost and Steel Slag Amendments Enhances Growth, Soil Health, and Drought Resilience in Durum Wheat Under Field Conditions - Farid Errouh; Lahoucine Ech-Chatir; Abdelhamid Aouabe; Chayma Ikan; Redouane Ouhaddou; Fatima-Ezzahra Soussani; Nizar El Mazouni; Julio Cesar Rodrigez; Salah Er-Raki; Hassan Chagiri; Hicham Khalisse; Brahim Oudra; et al. (Journal of Crop Health, 2025)

Bibliometric and review analysis of argan trees studies: global research trends and challenges - El Houcine El Moussaoui; Aicha Moumni; Saïd Khabba; Salah Er-Raki; Bouchra Ait Hssaine; Abdelghani Chehbouni; Abderrahman Lahrouni (Agroforestry Systems, 2025)

Physics-informed neural networks for enhanced reference evapotranspiration estimation in Morocco: Balancing semi-physical models and deep learning - Chouaib El Hachimi; Salwa Belaqziz; Saïd Khabba; Andre Daccache; Bouchra Ait Hssaine; Hasan Karjoun; Youness Ouassanouan; Badreddine Sebbar; Mohamed Hakim Kharrou; Salah Er-Raki; Abdelghani Chehbouni (Chemosphere, 2025)

A comparative methodological approach for argan forest classification using Landsat imagery - El Houcine El Moussaoui; Aicha Moumni; Saïd Khabba; Abdelhakim Amazirh; Salah Er-Raki; Abdelghani Chehbouni; Abderrahman Lahrouni (Environmental Monitoring and Assessment, 2025)

Beneficial microorganisms: a sustainable strategy to enhance morpho-physiological traits in drought-tolerant olive cultivars - Naira Sbbar; Soufiane Lahbouki; Salah Er-Raki; Allal Douira; Ahmed El Bakkali; Abderrahim Boutasknit; Cherkaoui El modafar; Abdelilah Meddich (Plant Biosystems, 2025)

Proxy detection of wheat water stress from photochemical reflectance index and land surface temperature data - Zoubair Rafi; Valérie Le Dantec; Saïd Khabba; Abdelhakim Amazirh; Patrick Mordelet; El Houssaine Bouras; Salah Er-Raki; Abdelghani Chehbouni; Olivier Merlin (Agricultural and Forest Meteorology, 2024)

Effects of regulated and sustained deficit irrigation on water use, physiology and yield of ‘Menara’ olive trees, in Morocco - Khaoula Ibba; Salah Er-Raki; Abdelaziz Bouizgaren; Rachid Hadria (Irrigation Science, 2024)

Irrigation optimization in green asparagus ( Asparagus officinalis L.) using the AquaCrop model and evolutionary strategy algorithms - Fidencio Cruz‐Bautista; Irineo Lorenzo López‐Cruz; Julio César Rodríguez; Andrés Ochoa‐Meza; Agustín Ruíz‐García; Salah Er‐Raki (Irrigation and Drainage, 2024)
Appropriate irrigation water management has attracted considerable attention because it is crucial to guarantee water and food security worldwide. This study aims to solve a water usage optimization problem for asparagus farming using the Deficit Irrigation Toolbox (DIT) optimization tool and AquaCrop‐OS model. Seven irrigation strategies were planned to assess the yield response of asparagus spears in the region near Caborca, Sonora, Mexico. Three of them were defined according to the usual practices of conventional irrigation, and the other four involved the optimization approach. Crop water productivity responses to 750, 1000, 1250 and 1500 mm of supplied water for the crop growing season were generated and assessed for each strategy. Using the irrigation optimization strategy, which involved a defined decision table using the covariance matrix adaptation evolutionary strategy, resulted in increased water productivity, making it the best solution to the optimization problem. A spear yield of 11.3–12.1 t ha −1 was obtained using an irrigation depth of 1200 mm, thus resulting in a reduced irrigation depth of 580–615 mm (>30%) for the 2019 growing season and 130–165 mm (±10%) for the 2020 growing season. The novelty of the study is that by formulating a dynamic optimization problem using the AquaCrop‐OS model and DIT, it is demonstrated that the water currently used for irrigation of asparagus crops can be reduced by up to 30%.

A sensitivity analysis of a FAO-56 dual crop coefficient-based model under various field conditions - Pierre Laluet; Luis Olivera-Guerra; Vincent Rivalland; Vincent Simonneaux; Jordi Inglada; Joaquim Bellvert; Salah Er-raki; Olivier Merlin (Environmental Modelling & Software, 2023)

Identifying gaps in actual and simulated/potential yield and growing season precipitation in Morocco - Terence Epule Epule; Abdelghani Chehbouni; Driss Dhiba; Daniel Etongo; Soumia Achli; Wiam Salih; Salah Er-Raki (Environmental Science and Pollution Research, 2022)

Integrating thermal stress indexes within Shuttleworth–Wallace model for evapotranspiration mapping over a complex surface - Jamal Elfarkh; Salah Er-Raki; Jamal Ezzahar; Abdelghani Chehbouni; Bouchra Aithssaine; Abdelhakim Amazirh; Saïd Khabba; Lionel Jarlan (Irrigation Science, 2021)

Assessment of Equity and Adequacy of Water Delivery in Irrigation Systems Using Remote Sensing-Based Indicators in Semi-Arid Region, Morocco - Mohamed Hakim Kharrou; Michel Le Page; Ahmed Chehbouni; Vincent Simonneaux; Salah Er-Raki; Lionel Jarlan; Lahcen Ouzine; Said Khabba; Ghani Chehbouni (Water Resources Management, 2013)